Atypical Presentation of Takotsubo Cardiomyopathy in an Elderly Woman - Priya Arunachalam; Nina Manian; Lamees Ibrahim El Nihum; Saleem Toro; John M. Buergler (Methodist DeBakey Cardiovascular Journal)
We describe an 83-year-old woman who presented to the emergency department with extreme thirst. Diagnostic testing revealed Takotsubo cardiomyopathy. Following symptomatic improvement and discharge, she returned to the emergency department with exudative pericardial effusion and elevated intrapericardial pressures. This case illustrates the importance of close follow-up of Takotsubo patients in whom complications such as pericardial effusion may lead to cardiac tamponade and hemodynamic instability if not managed properly.